C2H2 Zinc Finger Proteins: Master Regulators of Abiotic Stress Responses in Plants - Han, Guoliang; Lu, Chaoxia; Guo, Jianrong; Qiao, Ziqi; Sui, Na; Qiu, Nianwei; Wang, Baoshan (Frontiers in Plant Science, 2020)
Abiotic stresses such as drought and salinity are major environmental factors that limit crop yields. Unraveling the molecular mechanisms underlying abiotic stress resistance is crucial for improving crop performance and increasing productivity under adverse environmental conditions. Zinc finger proteins, comprising one of the largest transcription factor families, are known for their finger-like structure and their ability to bind Zn2+. Zinc finger proteins are categorized into nine subfamilies based on their conserved Cys and His motifs, including the Cys2/His2-type (C2H2), C3H, C3HC4, C2HC5, C4HC3, C2HC, C4, C6, and C8 subfamilies. Over the past two decades, much progress has been made in understanding the roles of C2H2 zinc finger proteins in plant growth, development, and stress signal transduction. In this review, we focus on recent progress in elucidating the structures, functions, and classifications of plant C2H2 zinc finger proteins and their roles in abiotic stress responses.